2021
DOI: 10.1111/jbi.14100
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography at the crossroad: Pleistocene range expansion throughout the Mediterranean and back‐colonization from the Canary Islands in the legume Bituminaria bituminosa

Abstract: Aim Species with widespread distributions offer excellent opportunities for investigating recent biogeographical patterns across broad scales. Here, we tested the hypothesis that, due to its intermediate geographical location, NW Africa is pivotal in explaining the phylogeographical patterns of taxa with Mediterranean–Macaronesian distributions using a legume species with short generation times. Location Mediterranean, with a focus on NW Africa and the Canary Islands. Taxon Pitch trefoil (Bituminaria bituminos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 87 publications
(134 reference statements)
2
17
0
Order By: Relevance
“…A process that could still be ongoing. Such an eastward expansion from refugia was also observed in other pan-Mediterranean legumes like narrow-leafed lupin ( Lupinus angustifolius ; Mousavi-Derazmahalleh et al, 2018) and pitch trefoil ( Bituminaria bituminosa ; García-Verdugo et al, 2021). The main difference between the Lupinus and Bitumenaria cases and wild peas is that the center of diversity of narrow-leafed lupin and pitch trefoil is located in the western rather than the eastern Mediterranean.…”
Section: Discussionsupporting
confidence: 55%
“…A process that could still be ongoing. Such an eastward expansion from refugia was also observed in other pan-Mediterranean legumes like narrow-leafed lupin ( Lupinus angustifolius ; Mousavi-Derazmahalleh et al, 2018) and pitch trefoil ( Bituminaria bituminosa ; García-Verdugo et al, 2021). The main difference between the Lupinus and Bitumenaria cases and wild peas is that the center of diversity of narrow-leafed lupin and pitch trefoil is located in the western rather than the eastern Mediterranean.…”
Section: Discussionsupporting
confidence: 55%
“…A process that could still be ongoing. Such an eastward expansion from refugia was also observed in other pan-Mediterranean legumes like Lupinus angustifolius (Mousavi-Derazmahalleh et al, 2018) and Bituminaria bituminosa (García-Verdugo et al, 2021). The main difference between the Lupinus and Bitumenaria cases and wild peas is that the centre of diversity of narrow-leafed lupin and pitch trefoil is located in the western rather than the eastern Mediterranean.…”
Section: Demographic Historymentioning
confidence: 61%
“…Intense research on plant phylogenetics and phylogeography over the last two decades have allowed the discovery of several major biogeographical trends in the Mediterranean basin (Garcia-Verdugo et al, 2021) and renewed our understandings of plant domestication (Purugganan, 2019). Following an initial focus on biogeographic refugia, recent studies have revealed the genetic imprints of past expansions and migration processes, some involving the entire Mediterranean basin (see reviews in Medail and Diadema 2009;Nieto Feliner 2011;Nieto Feliner, 2014;Migliore et al, 2018;Vargas et al, 2018;Thompson, 2020;Garcia-Verdugo et al, 2021). Our study provides a better understanding of the phylogeography of Mediterranean plants by revealing a new historical scenario: the main gene pools of carob (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As for several crops, the Near East and the Eastern Mediterranean were initially proposed as the center of domestication for the carob tree (Zohary, 2002;Ramon-Laca and Mabberley, 2004). However, a recent multidisciplinary phylogeographic study based on wild and cultivated carob trees revealed the existence of four main genetic groups across the Mediterranean with a strong west-east structure (Viruel et al, 2020), which has also been documented for other Mediterranean plants (Désamoré et al 2011;Nieto Feliner 2014;Chen et al 2014;Migliore et al 2018;Garcia-Verdugo et al 2021). Using coalescent simulations based on microsatellite data, the estimated divergence times between these genetic groups pre-date the Neolithic origin of agriculture (Viruel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%